Genetic Variation within «Phaeoacremonium aleophilum» and «P. chlamydosporum» in Italy - Santilli, Elena; Bertelli, Emanuela; Surico, Giuseppe; Tegli, Stefania (Phytopathologia Mediterranea, 2000)
Genetic variation among isolates of Phaeoacremonium chlamydosporum (Pch) and P. aleophilum (Pal),two hyphomycetous fungi involved in the development of symptoms of esca and in a decline of young grapevines, wasstudied in eight Italian grapevine growing regions. Genetic variation was estimated by analysis of amplificationprofiles obtained in RAPD- and RAMS-PCR experiments (RAPD = Random Amplified Polymorphic DNA; RAMS =Random Amplified Micro- or Mini-Satellites). The genetic divergence between the two species suggests their assignmentto two different genera. Within each species, a low level of polymorphism was found; however a higher degreeof genetic variation was found with RAPD than with RAMS experiments, and more with Pal than with Pch isolates.No relationship was found for either species between the clustering of isolates in statistically defined groups and thegeographic origin of those isolates. A low level of genetic disequilibrium was found in Pch and Pal, suggesting thatsexual reproduction may occur in both fungi.